EDUCAÇÃO FÍSICA E INCLUSÃO ESCOLAR: UM OLHAR SOBRE O PLANO MUNICIPAL DE EDUCAÇÃO E A MATRIZ CURRICULAR DE EDUCAÇÃO FÍSICA NA PERSPECTIVA DA INCLUSÃO - Distefano, Fabiane (2014)
This study aims to focus on the analysis of tenets of legal and guiding documents of Education / Physical Education, from the municipal public system of education of the city of Ponta Grossa - PR, regarding the inclusion of students with disabilities. The main question we sought to answer in this study was: What are the tenets of legal and guiding documents of Education/ Physical Education, on a view of the inclusion of students with disabilities, from the municipal public school system of the city of Ponta Grossa - PR? For the theoretical foundation of the research it was used the following studies: Santos (1999) to debate about the multicultural construction of equality and difference, Gomes Almeida & Bracht (2010) to discuss the differences and challenges of Physical Education at school, Bauman (2010, 1999) to discuss about modernity, Rodrigues (2010), Mendes (2006), Costa (2010) and Mittler (2003) to address inclusive education, Cruz (2008), and Chicon (2007), to discuss Inclusive Physical Education. The investigation was based upon contents analysis by Bardin (1977) and it analyzed the Municipal Education Plan of the city of Ponta Grossa (PMEPG, 2008- 2018) and the Course Curriculum for Physical Education of the City of Ponta Grossa - PR (MCEFPG, 2013) . The documents analyzed were obtained under the authorization of the Municipal Board of Education of the city of Ponta Grossa. In regard to the Municipal Education Plan, it was found that it adopts the perspective of total inclusion. However, it is clear the absence of a debate in face of the accumulated theoretical framework, as for, the document does not appertain to how the inclusion will effectively occur within the school. Heading to the same direction, the Course Curriculum for Physical Education likewise, does not present a theoretical framework capable of offering a base for the discussion about inclusion, as in many occasions, its proposed contents and objectives are transcripts of the Parameters of the National Curriculum, requiring a major depth to support the pedagogical work of the teacher with students with disabilities.